Preliminary investigation of the molecular pathogenicity determinants of Xanthomonas campestris pv. zeae - Downing, T G (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1998)
Xanthomonas campestris pv. zeae was shown to posses a vast range of potential plant cell wall degrading enzymes including at least one protease, a carboxymethylcellulase, pectin lyase, polygalacturonase and a B-endoglucanase. Replicon stability and transfer system efficiencies were determined for a range of oriC, and oriT -tra combinations, and suitable vectors were constructed and identified for insertional inactivation by homologous recombination. Ideal suicide replicons were found to be pACYC184 and p15A, while P, Wand Q group replicons were supported by X campestris pv. zeae. Group P and group N transfer systems were shown to be highly efficient in intra-genus matings between Escherichia coli and X campestris pv. zeae, with the exception of P-tra systems in trans for the delivery of Tn5. Various cloning vectors were tested for stability and mobility. Tn5 was shown to transpose at high frequencies into the genome of the bacterial plant pathogen, and insertion was relatively random. Suitable screening assays were established to allow rapid isolation of mutants with potential virulence or pathogenic deviations, after mutagenesis. Two non-pathogenic mutants were identified, one of which was a putative hrpÂ·, while the other was a leaky virulence. A single mutant showing 40% reduced protease activity was also shown to exhibit reduced virulence indicating a minor role for the protease in pathogenicity. The majority of virulence mutants showed altered growth in different levels of nutritional availability and complexity. Nutritional viability (the ability to acquire and use nutrients at a sufficient rate to grow fast enough to overcome host defences) was shown to be essential for virulence and possibly pathogenicity. Wild-type in-planta behaviour was analysed and growth and spread patterns typical for pathogenic response identified. Chief amongst these was the requirement for a threshold level of cells per leaf area or length, before symptoms could develop. Occlusion of vascular bundles was shown not to be the primary factor in the pathogenicity of X campestris pv. zeae. Threshold levels for lesion development indicate the absence of a diffusable lesion forming element, and possibly the requirement of cell density for induction of certain functions.,KMBT_363
Keywords: Uncatalogued